2019
DOI: 10.3390/v11030241
|View full text |Cite
|
Sign up to set email alerts
|

Directed in Vitro Evolution of Therapeutic Bacteriophages: The Appelmans Protocol

Abstract: The ‘Appelmans protocol’ is used by Eastern European researchers to generate therapeutic phages with novel lytic host ranges. Phage cocktails are iteratively grown on a suite of mostly refractory bacterial isolates until the evolved cocktail can lyse the phage-resistant strains. To study this process, we developed a modified protocol using a cocktail of three Pseudomonas phages and a suite of eight phage-resistant (including a common laboratory strain) and two phage-sensitive Pseudomona aeruginosa strains. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(171 citation statements)
references
References 54 publications
2
139
2
Order By: Relevance
“…Could our understanding of phage biology be correct when most experiments investigated an artificial group consisting of only a single type of phage? Consistent with the idea that our experimental approaches may have masked the true nature of phage biology, is the finding by a number of groups that a bacteriophage population is capable of broadening their host range [93][94][95]. Such findings would argue away from the current paradigm that bacteriophage targets only a narrow, fixed range of bacteria.…”
Section: Summary and Future Directionssupporting
confidence: 69%
“…Could our understanding of phage biology be correct when most experiments investigated an artificial group consisting of only a single type of phage? Consistent with the idea that our experimental approaches may have masked the true nature of phage biology, is the finding by a number of groups that a bacteriophage population is capable of broadening their host range [93][94][95]. Such findings would argue away from the current paradigm that bacteriophage targets only a narrow, fixed range of bacteria.…”
Section: Summary and Future Directionssupporting
confidence: 69%
“…Such changes lead to altered structural gene products, for example, encoding phage tail fiber assembly proteins that are necessary for phage attachment to the host cell or adsorption, which is the first step of phage infection. Adaptation can also reduce lysis time and increase phage burst size [ 43 , 44 ]. Recent findings on the Eliava Staphylococcal Bacteriophage cocktail that consist of Twort-like phage Sb-1 showed that after the adaptation process, newly formed phage clones were found in phage stock, and such a process increased phage lytic activity from 87% to 96% on globally diverse S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratory adaptation and genetic engineering of phages for therapeutic purposes is likely to be a significant force that will transform phage therapy [13,36,45,46], and the latter is already a commercial focus in the United States for companies such as Locus Biosciences and Armata Pharmaceuticals. In vitro evolution (or phage adaptation, phage training) to expand or optimize host range is an approach to modify and improve phages that has been used extensively in former Soviet countries and Eastern Europe, and was recently described in the Western literature [37,[47][48][49]. Alteration of phage host range by this approach can also potentially be used to discover novel molecular mechanisms that can be exploited for genetic modification strategies [50].…”
Section: Approaches For Phage Therapeutic Designmentioning
confidence: 99%